Reliability Study on"Practical Process Evaluation Scale"in Class of Traditional Manipulation Techniques - Lili LIN; Kexiang XU; Jun LIAO; Zhiqiang WANG; Dong LIN (康复学报)
Objective:To analyze the reliability of"Practical Process Evaluation Scale"and further more to get the most relevant factors in class of traditional manipulation techniques.Methods:Students were assigned to different groups (three students in each group) in the class of traditional manipulation techniques about the"one-finger scrubbing". The operator scale, model scale and observer scale were designed respectively. In each section, three scales should be completed by three students in each group according to three different roles which was arranged before. This practice was continued for eight weeks, once a week.Results:The reliability analysis showed that the Cronbach's coefficient of operator scale was 0.891, the Cronbach's coefficient of model scale was 0.941, the Cronbach's coefficient of observer scale was 0.774, and the Cronbach's coefficient of total scale was 0.894. The data showed that these scales were high confidence, and have a high internal consistency. The scale factor analysis showed that the most relevant factors in class of traditional manipulation techniques were strength factor, mind factor and limbs factor.Conclusion:In the class of traditional manipulation techniques, "Practical Process Evaluation Scale"is a high-confidence scale, which could accord with the teaching rules of practical training and help to improve students'practical ability, and the most relevant factors should be paid attention to, so as to improve teaching quality effectively.